Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Petani Padi Di Kabupaten Lamongan - Fajar Annas; Sri Muljaningsih; Kiky Asmara (Ecobuss, 2021)
Income is a very important thing in determining the profit or loss is obtained by making a comparison between the income and expenses incurred on the income. One of the main economic indicator to measure the economic capacity of the community is the level of community income. The development of agriculture in Indonesia when viewed from the period of experincing ups and downs, when viewed farmers income is currently a very serious problem because the income earned by farmers is always changing caused by various factors. This study uses a quantitative descriptive approach. The data sources for this research are observations, interviews, literature studies, data collection (questionnaires) and Statistics of Laamongan Regency. The results showed that the variables of land area simultaneously through production, production cost and selling price had a significant and positive effect on farmers income. And partially land area through production results, production cost and selling prices have a significant and positive effect on farmers income in the village of Bakalrejo Sugio sub District Lamongan District.